URBAN FARMING: MEMBANGUN KESADARAN DAN KEMANDIRIAN MASYARAKAT DALAM MENGHASILKAN PANGAN LOKAL - Hidayat, Wahyu; Yusuf Q, Muhammad; Lamane, Siti Aisa; MA, Andi Maharani; Gunadi, Ahmad (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
People in urban areas are affected by shifts in lifestyles, lifestyles and poor management of resources. One example is urban people spending money on daily needs by buying goods in the market. On the other hand, people do not tap into the potential that is around them. For example, they leave idle land, unproductive land, and idle yard land. One solution is to implement Urban Farming. Urban farming activities can provide many benefits as a way to meet household needs and increase family income if utilized properly. Yard land can help families get food, reduce household costs, and increase household income. Urban farming activities still face a number of challenges related to social, cultural, and economic problems. Among these challenges is the lack of awareness of intensive yard cultivation. The purpose of this service is to form a Peasant Women's Group (KWT) that is able to motivate the community to have the will to use idle land and yard land, to meet food needs and increase family income. Service activities were carried out in RW04 Area, Rampoang Village, Bara District, Palopo City. The results of this dedication are expected to gradually change consumptive behavior in a productive direction, which means more food for the family, less household expenses, and more money for the family.